Let's begin by listing out the information given to us:
The figure before us is triangle. It is worth noting that the sum of angles in a triangle is 180 degrees
![\begin{gathered} m\angle L=70^(\circ) \\ m\angle M=50^(\circ) \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/nn1lbeyt0glwcq5jpfc6romjccr3cke5ed.png)
To find the angle at K (m∠LKM), we will subtract the sum of angles L & M from 180 degrees (the sum of angles in a triangle). We have:
![\begin{gathered} m\angle LKM=180-(m\angle L+m\angle M) \\ m\angle LKM=180-(70+50)=180-120=60 \\ m\angle LKM=60^(\circ) \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/eqmh0hynlua8kyllx7bf24yyivvp6v3y33.png)
To find the angle at LKN (m∠LKN), we will subtract angle LKM from 180 degrees (the sum of angles on a straight line). We have:
![\begin{gathered} m\angle LKN+m\angle LKM=180^(\circ) \\ m\angle LKM=60^(\circ) \\ m\angle LKN+60=180 \\ m\angle LKN=180-60=120 \\ m\angle LKN=120^(\circ) \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/wuaxijud4yw4aoekn2firo3933te2pahms.png)
Therefore, m∠LKN is equal to 120 degrees